Study on the mechanism of KIF18B affecting the malignant progression of glioblastoma cells - Su, Xiangyue; Huang, Liji; Ma, Wei; Wang, Rong; Zeng, Xiangjian; Wei, Gangliang; Mai, Suli; Yang, Min; Tang, Shifu (Frontiers in Genetics, 2025)
BackgroundMember of the driver protein family 18B (KIF18B) is a potential prognostic marker and is highly expressed in a variety of cancers. However, its function in glioblastoma (GBM) remains unclear.MethodsThe expression data of KIF18B were obtained by accessing TCGA, CGGA and GEPIA databases, and verified by Western blot assay and immunohistochemistry. Glioma RNA sequencing data and clinical information were downloaded from TCGA and CGGA databases, and Kaplan-plotter survival analysis and Multivariable COX regression analysis were performed to plot ROC survival curves at 1, 3 and 5 years cBioPortal and MethSurv were used to carefully examine the prognostic value of KIF18B methylation. CBioPortal database and UALCAN database were used to obtain KIF18B co-expressed genes for GO and KEGG enrichment analysis, and gene set enrichment analysis (GSEA) software was used to explore the signaling pathway of KIF18B regulation of GBM. Finally, the correlation between KIF18B and GBM infiltration was studied by using TIMER database and TCGA dataset.ResultsKIF18B was highly expressed in various cancers including GBM, and was positively correlated with glioma grade and negatively correlated with prognosis. Multivariable COX regression analysis and ROC curve showed that KIF18B was one of the independent risk factors for glioma prognosis. KIF18B methylation was negatively correlated with KIF18B expression, and the overall survival rate of patients with KIF18B hypomethylation was lower than that of patients with KIF18B hypermethylation. A total of 124 co-expressed genes were selected from the database. KEGG pathway analysis showed that KIF18B was mainly involved in the malignant progression of glioma through P53 and other signaling pathways. GSEA analysis showed that the high expression group of KIF18B was mainly enriched in E2F, G2M and other signaling pathways. The results of immunoassay showed that the expression of KIF18B was correlated with immune infiltration of tumor microenvironment.ConclusionKIF18B is a key factor affecting the prognosis of GBM patients, and its targeting may provide a new therapeutic method for GBM patients.